Studies On Photocatalytic Degradation Of Phenol In Aqueous Solution.2004 - Ab Rahim, Siti Kartini (2004)
Photocatalytic destruction of phenol in aqueous solution was studied in this work. A batch reactor using an ultraviolet lamp with wavelength of 254 nm as a source of energy to excite photocatalysts was fabricated.